Association of transforming growth factor-β1 gene polymorphism in the development of Epstein-Barr virus-related hematologic diseases - Kanako Hatta; Akira Morimoto; Eiichi Ishii; Hiroshi Kimura; Ikuyo Ueda; Shigeyoshi Hibi; Shinjiro Todo; Tohru Sugimoto; Shinsaku Imashuku (Haematologica, 2007)
Background and Objectives Epstein-Barr virus (EBV) is etiologically associated with various hematologic disorders, including primary acute infectious mononucleosis (IM), hemophagocytic lymphohistiocytosis (EBV-HLH), chronic active EBV infection (CAEBV) and malignant lymphomas. Although cytokines play a central role in EBV-related immune responses, the exact mechanisms causing different clinical responses remain unclear. In this study, the pattern of cytokine gene polymorphisms was comparatively analyzed in EBV-related diseases.Design and Methods Eighty-nine patients with EBV-related disease were analyzed; 30 with IM, 28 with EBV-HLH and 31 with CAEBV. Eighty-one EBV-seropositive healthy adults were also used as controls. Associations with polymorphisms of various cytokines, including interleukin (IL)-1α and IL-1β were evaluated. The gene polymorphisms were typed by polymerase chain reaction with sequence-specific primers.Results A significant difference of polymorphisms was found for transforming growth factor (TGF)-β1; the frequency of TGF-β1 codon 10 C allele was significantly higher in patients with EBV-related diseases than in controls (p<0.001). The difference was significant in patients with IM or HLH (p<0.001), but not in those with CAEBV (p=0.127), compared with controls. As regards other cytokines, the frequency of the IL-1α –889 C allele was significantly lower in patients with IM than in controls (p<0.05).Interpretation and Conclusions Our results suggests that TGF-β1 codon 10 C allele plays a role in the development of EBV-related diseases and that the IL-1α –889 C allele may be involved in response failure and sequential progression into the development of HLH.